Effects of lumbar extensor muscle strengthening and neuromuscular control retraining on disability in patients with chronic low back pain: a protocol for a randomised controlled trial. Issue 8 (19th August 2019) - Farragher, Joshua Brodie; Pranata, Adrian; Williams, Gavin; El-Ansary, Doa; Parry, Selina M; Kasza, Jessica; Bryant, Adam
Abstract : Introduction: Chronic low back pain (CLBP) is the leading cause of disability worldwide. However, there is no consensus in the literature regarding optimal management. Exercise intervention is the most widely used treatment as it likely influences contributing factors such as physical and psychological. Literature evaluating the effects of exercise on CLBP is often generalised, non-specific and employs inconsistent outcome measures. Moreover, the mechanisms behind exercise-related improvements are poorly understood. Recently, research has emerged identifying associations between neuromuscular-biomechanical impairments and CLBP-related disability. This information can be used as the basis for more specific and, potentially more efficacious exercise interventions for CLBP patients. Methods and analysis: Ninety-four participants (including both males and females) with CLBP aged 18–65 who present for treatment to a Melbourne-based private physiotherapy practice will be recruited and randomised into one of two treatment groups. Following baseline assessment, participants will be randomly allocated to receive either: (i) strengthening exercises in combination with lumbar force accuracy training exercises or (ii) strengthening exercises alone. Participants will attend exercise sessions twice a week for 12 weeks, with assessments conducted at baseline, midway (ie, 6 weeks into the trial) and at trial completion. All exercise interventions will be supervised by a qualified physiotherapist trained in the intervention protocol. The primary outcome will be functional disability measured using the Oswestry Disability Index. Other psychosocial and mechanistic parameters will also be measured. Ethics and dissemination: This study was given approval by the University of Melbourne Behavioural and Social Sciences Human Ethics Sub-Committee on 8 August 2017, reference number 1 749 845. Results of the randomised controlled trial will be published in peer-reviewed journals. Trial registration number: ACTRN12618000894291.